A contribution of axiomatic design principles to the analysis and impact of attacks on critical infrastructures - Palleti V.R. (Elsevier B.V., 2023)
Models; Public works; Water supply systems; Abstract representation; Attacks; Axiomatic design; Axiomatic design theory; Critical infrastructure protection; Detection of attacks; Economic prosperity; Water distributions; Critical infrastructures